Effects of tourniquet inflation on peri- and postoperative cefuroxime concentrations in bone and tissue - Hanberg, Pelle; Bue , Mats; Kabel, Jesper; Jørgensen, Andrea René; Jessen, Christian; Søballe, Kjeld; Stilling, Maiken (Acta Orthopaedica, 2021)
Background and purpose — Tourniquet is widely used in orthopedic surgery to reduce intraoperative bleeding and improve visualization. We evaluated the effect of tourniquet application on peri- and postoperative cefuroxime concen- trations in subcutaneous tissue, skeletal muscle, calcaneal cancellous bone, and plasma. The primary endpoint was the time for which the free cefuroxime concentration was maintained above the clinical breakpoint minimal inhibitory concentration (T > MIC) for Staphylococcus aureus (4 μg/mL). Patients and methods — 10 patients scheduled for hallux valgus or hallux rigidus surgery were included. Microdialysis catheters were placed for sampling of cefurox- ime concentrations bilaterally in subcutaneous tissue, skel- etal muscle, and calcaneal cancellous bone. A tourniquet was applied on the thigh of the leg scheduled for surgery (tourni- quet duration time [range]: 65 minutes [58–77]). Cefuroxime (1.5 g) was administered intravenously 15 minutes prior to tourniquet inflation, followed by a second dose 6 hours later. Dialysates and venous blood samples were collected for 12 hours. Results — A cefuroxime concentration of 4 μg/mL was reached within 23 minutes in all compartments and patients. For cefuroxime the T > MIC (4 μg/mL) ranged between 4.8 and 5.4 hours across compartments, with similar results for the tourniquet and non-tourniquet leg. Comparable T > MIC and penetration ratios were found for the first and second dosing intervals. Interpretation — Administration of cefuroxime (1.5 g) 15 minutes prior to tourniquet inflation is safe in order to achieve tissue concentrations above 4 μg/mL throughout surgery. A tourniquet application time of approximately 1 hour did not affect the cefuroxime tissue penetration in the following dosing interval.